Tata Kelola Pemerintahan Desa Berbasis Good Governance dalam Pengembangan Desa Mandiri (Studi Kasus di Desa Patik, Kabupaten Ponorogo) - Khoirun Nisa’; Sri Roekminiati; Dandy Patrija Wiraman (Universitas 45 Surabaya, 2025)
This study aims to determine how the principles of good governance are applied in village administration and their role in supporting Patik Village in becoming an Independent Village. The study uses a qualitative approach through interviews, observations, and document studies. The results show that the participation, accountability, and responsiveness of the village government have been effective. Community participation is evident from the active involvement of residents in deliberations and cooperation in road construction. Accountability is reflected in the submission of village reports, while the responsiveness of the village government is evident in its swift action to repair agricultural infrastructure, which has a direct impact on the economic efficiency of farmers. However, transparency is still not optimal due to the village information system (SID) not yet being fully operational digitally. In addition, field results show that strengthening ecological resilience through piping, construction of infiltration wells, and utilization of the Pakel Reservoir also contributes to the sustainability of the village environment. Thus, the implementation of good governance supports the strengthening of social, economic, and ecological resilience as the main pillars of the Village Development Index (IDM), and is an important foundation for Patik Village's achievement of becoming an Independent Village.